Performance profiling in strength and conditioning - Johnson, D.; Bird, M. (Strength and Conditioning Journal, 2022)
Performance profiling is a client-led assessment tool that enables athletes to uncover strengths and weaknesses associated with their sporting performance. Initially designed to increase client commitment to a training program, the performance profiling technique presents an opportunity for the athlete to play an active role and contribute to the initial needs analysis process. This evidenced-based method of assessment has been shown to help clients increase their self-awareness, identify areas they can improve, and serve as a basis for goal setting. The tool also permits both client and practitioner to monitor and track progress over time. Although predominantly adopted for those providing psychological support to athletes, the performance profile may be beneficial for strength and conditioning coaches. This article aims to highlight the potential benefits of performance profiling within the field of strength and conditioning, provides guidelines with completed examples for strength and conditioning practitioners to integrate into their work with clients, and presents a brief overview of the theory underpinning the technique.